Treatment of Chest Wall Sarcomas: A Single-institution Experience Over 20 Years. (February 2015) - Burt, Ashley; Berriochoa, Jacob; Korpak, Anna; Rodler, Eve; Jones, Robin L.; Weisstein, Jason; Patel, Shilpen
Abstract : Objective: To evaluate the impact on the outcome of radiation therapy and chemotherapy in the treatment of localized chest wall sarcomas. Methods: A retrospective review of 65 patients with stage IIB and III chest wall sarcomas seen over 20 years at the University of Washington Medical Center. Overall and disease-free survival outcomes were analyzed on the basis of the treatment received: surgery alone; surgery and radiation therapy; surgery and chemotherapy; and surgery, radiation therapy, and chemotherapy. Results: Disease recurrence was observed in 32.3%, and, of these, 33.3% were local only, 42.9% distant only, and 23.8% were both local and distant. As compared with surgery alone, disease-free survival at both 5 and 10 years improved by 92% with the addition of radiation therapy to surgery, by 82% with the addition of chemotherapy to surgery, and by 89% and 90% with the addition of both chemotherapy and radiation therapy at 5 and 10 years, respectively. Overall survival also improved with radiation therapy, chemotherapy, or the combination of both, with the greatest improvement seen in patients treated with both radiation therapy and chemotherapy, which showed reduced mortality at 5 and 10 years of 49% and 45%, respectively, compared with surgery alone. Conclusions: The addition of radiation therapy, chemotherapy, or both to surgery in localized chest wall sarcoma improves outcome and should strongly be considered for patients with acceptable comorbidities. A trend toward improvement in overall survival was also shown with the use of radiation therapy and chemotherapy. As chest wall sarcomas are rare and histologically heterogenous, larger studies are necessary to elucidate which histologic subtypes may gain the most benefit from radiation therapy and chemotherapy.